Tungsten porous material, its preparation method and application
Patent Information
- Application Number
- CN202410357239.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-03-27
AI Technical Summary
[0003]金属钨的维氏硬度3430MPa,泊松比0.28,杨氏模量411GPa,因此,金属的硬度大,脆性强,使用粉末冶金的方法压制多孔钨坯体的过程中极易开裂
Smart Images

Figure CN118341976B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of tungsten materials technology, specifically relating to a porous tungsten material, its preparation method, and its application. Background Technology
[0002] Porous materials possess characteristics such as low specific gravity, large specific surface area, good absorption of energy and electromagnetic waves, flame retardancy, high heat exchange and dissipation capacity, good sound absorption, excellent permeability, heat and fire resistance, and thermal shock resistance. Porous tungsten materials, in addition to the characteristics of porous metallic materials, also possess the properties of tungsten, such as high melting point and high density. Tungsten-copper high-strength, high-conductivity alloys, made by impregnating copper into porous tungsten materials, combine the advantages of both tungsten and copper, exhibiting high high-temperature strength, high electrical conductivity, high thermal conductivity, high hardness, low coefficient of thermal expansion, resistance to electrolytic corrosion, and certain plasticity. In civilian devices, tungsten-copper alloys are widely used in electrical contacts, electrodes, substrates, inserts, connectors, and heat dissipation elements in large-scale integrated circuits and high-power microwave devices; in the military, they are used to manufacture high-temperature resistant components such as throat liners, gas turbine rotors, and nose cones for various missiles. Emitters made by immersing emission materials in porous tungsten materials have characteristics such as high emission current density, long lifespan, and high temperature resistance. This makes porous tungsten or various components made from porous tungsten parts widely used in aerospace, power electronics, and metallurgical industries.
[0003] Tungsten metal has a Vickers hardness of 3430 MPa, a Poisson's ratio of 0.28, and a Young's modulus of 411 GPa. Therefore, its high hardness and brittleness make it highly susceptible to cracking during the pressing of porous tungsten blanks using powder metallurgy. Furthermore, while tungsten metal has a melting point of 3410℃, the sintering temperature of powder metallurgy is approximately 0.7–0.8 times the melting point of tungsten. For tungsten, the sintering temperature is as high as 2387–2728℃, which is difficult for ordinary sintering furnaces to meet. During the molding process of porous tungsten materials prepared using powder metallurgy, weak physical interlocking forces between powder particles can lead to loosening of the powder, resulting in poor metallurgical bonding strength during sintering. This can cause powder detachment during use, leading to adverse consequences. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention proposes a method for physically and chemically modifying quasi-spherical polyhedral high-purity tungsten powder. This process forms a chromium layer on the surface of the tungsten powder, which then forms a tungsten-chromium solid solution during the subsequent sintering process. Furthermore, during high-temperature sintering, the active sites between the powder particles undergo further diffusion reactions, forming numerous network sintering necks that enhance the metallurgical bonding strength between the tungsten powder particles, thereby preventing the tungsten powder from falling off during use.
[0005] One of the objectives of this invention is to provide a tungsten porous material, which is a pre-formed powder particle with a core-shell structure. The pre-formed powder particle includes a spherical tungsten core layer, a chromium shell layer, and a tungsten-chromium solid solution sintering neck formed between the spherical tungsten core layer and the chromium shell layer by high-temperature sintering.
[0006] In the tungsten porous material, the molar ratio of tungsten to chromium is (2-10):1, preferably (4-9):1.
[0007] The tungsten porous material has an average pore size of 0.5–5 μm and a porosity of 10–50%; preferably, the tungsten porous material has an average pore size of 0.5–3 μm and a porosity of 10–40%.
[0008] The second objective of this invention is to provide a method for preparing the above-mentioned porous tungsten material, comprising: dispersing or dissolving spherical tungsten powder and soluble chromium salt in ultrapure water, adding ammonia solution to react, and then reducing, grinding, pressing, and sintering the obtained solid powder at high temperature to obtain the porous tungsten material.
[0009] The preparation method of the tungsten porous material specifically includes the following steps:
[0010] (1) Disperse near-spherical tungsten powder in ultrapure water, dissolve it in soluble chromium salt, and then add ammonia solution dropwise, strictly controlling the OH content during the addition process. - With Cr 3+ The molar ratio, stirring reaction;
[0011] (2) After the reaction mixture is filtered, washed and dried, it is reduced in a reducing atmosphere to obtain tungsten-chromium core-shell preformed powder.
[0012] (3) Grind the tungsten-chromium core-shell pre-made powder. The purpose of grinding is to avoid the powder from sticking and clumping during the hydrogen reduction process. Then, use a mold to fill and press the ground and dried pre-made powder to obtain a tungsten porous material green body.
[0013] (4) Clean the floating powder on the surface of the pressed green body and sinter it in a sintering furnace to obtain the tungsten porous material.
[0014] In step (1) of the above method for preparing tungsten porous materials:
[0015] The spherical tungsten powder has a Fisher particle size of 3–20 μm, preferably 5–10 μm; compared with spherical tungsten powder, the spherical tungsten powder has the characteristics of good formability and strong flowability.
[0016] The mass ratio of the spherical tungsten powder to ultrapure water is 1:(1-10), preferably 1:(1-5);
[0017] The soluble chromium salt is selected from at least one of chromium chloride, chromium sulfate, and chromium nitrate;
[0018] The molar ratio of tungsten in the spherical tungsten powder to chromium in the soluble chromium salt is (2-10):1, preferably (4-9):1;
[0019] The concentration of the ammonia solution is 0.2–2.0 mol / L, preferably 0.2–1 mol / L;
[0020] The aforementioned soluble chromium salts react with ammonia (NH3·H2O) to form chromium hydroxide (Cr(OH)3). However, chromium hydroxide, being an amphoteric hydroxide, is soluble in weak alkalis. To prevent chromium hydroxide from dissolving again in the ammonia solution, its reaction stoichiometry must be strictly controlled during the reaction. Specifically, the dropping rate of the ammonia solution should be 5–10 mL / min, and the Cr content should be controlled accordingly. 3+ With OH - The molar ratio is 1:(1-3), preferably 1:(2-3);
[0021] The stirring reaction time is 150–300 min.
[0022] In step (2) of the above method for preparing tungsten porous materials:
[0023] The drying conditions are: temperature 100-150℃, time 2-4 hours;
[0024] The reducing atmosphere is a hydrogen atmosphere;
[0025] The reduction treatment conditions were: hydrogen flow rate of 1–6 L / min, temperature of 900–1200 °C, and time of 3–8 h.
[0026] In step (3) of the above method for preparing tungsten porous materials:
[0027] The grinding process employs ball milling, preferably using a planetary ball mill for wet ball milling to break up any agglomerated powder particles formed during hydrogen reduction. The wet ball milling operation can be performed using commonly used wet ball milling methods in the prior art. For example, the specific ball milling method can be as follows: a zirconia ball milling jar is used, with zirconia balls having a diameter of 5 mm and a powder loading of 50 g, resulting in a ball-to-powder ratio of 1:1. Anhydrous ethanol is added to the grinding jar to cover the grinding balls and powder. After securing the grinding jar, argon gas is introduced, and the ball milling speed is 100 r / min.
[0028] The mold can be a commonly used mold in the prior art, for example, a silicone mold or a rubber mold;
[0029] The pressing and molding process is carried out using a cold isostatic press. Preferably, the pressing and molding conditions are: pressure of 170-240 MPa, holding time of 3-10 min, and pressurization time of 30-50 min.
[0030] In step (4) of the above method for preparing tungsten porous materials:
[0031] The sintering atmosphere is hydrogen;
[0032] The sintering conditions are: temperature of 1700–2100℃, time of 3–6h, and hydrogen flow rate of 300–600L / min.
[0033] According to a specific embodiment of the present invention, the tungsten porous material can be prepared by the following specific steps:
[0034] a) Weigh out spherical tungsten powder and ultrapure water, place them in a round-bottom flask to prevent the tungsten powder from being oxidized in the subsequent reaction, reflux using a condenser and treat the exhaust gas, and disperse the tungsten powder by magnetic stirring.
[0035] b) Weigh the soluble chromium salt and pour it into a round-bottom flask containing tungsten powder. Stir at high speed for 2-5 hours to completely dissolve it in ultrapure water.
[0036] c) Prepare an ammonia solution and add it dropwise into a round-bottom flask containing tungsten powder. Stir for 2-5 hours to ensure the solution is fully mixed. Once the reaction is complete, Cr(OH)3 will be generated in the solution. These precipitates can adhere well to the surface of the tungsten powder.
[0037] CrCl3+3NH3·H2O=Cr(OH)3↓+3NH4Cl
[0038] d) Filter the powder using filter paper and rinse it with ultrapure water to remove any possible NH4Cl, thus avoiding affecting the bonding between powders during sintering; then heat and dry.
[0039] e) The powder obtained above is reduced in a hydrogen atmosphere using a tube furnace at a reduction temperature of 900-1200℃, a hydrogen flow rate of 1-6L / min, and a reduction time of 3-8h, so that the hydroxide is reduced to elemental metal and Cr can adhere well to the surface of tungsten powder.
[0040]
[0041]
[0042] f) Grind the powder obtained above and shape it using a mold. The molding pressure is 170-240 MPa, the holding pressure is 3-10 min, and the pressurization time is 30-50 min to obtain a porous tungsten blank with high strength.
[0043] g) Clean the surface powder of the pressed green body, and sinter it in a high-temperature atmosphere furnace. The sintering atmosphere is hydrogen, the sintering temperature is 1700-2100℃, and the holding time is appropriate for 3-6 hours. Cr and W can react to form W-Cr solid solution (W 0.7 Cr 0.3 W 0.5 Cr 0.5 W 0.4 Cr 0.6 The solid solution can form a good metallurgical bond between tungsten powders, thereby forming a good sintering neck. The solid solution formed at the sintering neck contains Cr, which, after oxidation, can form a dense Cr2O3 layer, which can effectively resist oxidation at the sintering neck and improve the oxidation resistance of porous tungsten materials.
[0044] A third objective of this invention is to provide the application of the tungsten porous material described in the first objective of this invention or the tungsten porous material obtained by the preparation method described in the second objective of this invention in metal binders.
[0045] In this invention, chromium is used as an additive. It is coated onto the surface of tungsten powder through physical and chemical methods, making it a metal binder. Cr and W both have body-centered cubic crystal structures, and Cr and W have similar atomic radii (Cr atomic radius is 0.185 nm, W atomic radius is 0.137 nm), which can form an infinite substitution solid solution. During sintering, a W-Cr solid solution is formed, which has good interfacial bonding strength, resulting in higher strength of the sintering necks formed between the tungsten powder particles. Attached Figure Description
[0046] Figure 1 An electron microscope image of spherical tungsten powder.
[0047] Figure 2 XRD analysis of powders coated with W and reduced by hydrogen at different reduction temperatures using Cr(OH)3.
[0048] Figure 3 The image shown is an electron microscope image of the porous tungsten material obtained in Example 1.
[0049] Figure 4a ~b is the elemental analysis diagram of the tungsten porous material obtained in Example 1. Detailed Implementation
[0050] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0051] The testing instruments and conditions used in this embodiment are as follows:
[0052] Testing standards:
[0053] GB / T 5249-2013 Determination of Pore Size in Permeable Sintered Metal Materials (Bubble Test)
[0054] GB-T7314-2005 Metal Compression Test Method
[0055] Testing instruments:
[0056] DH-200M High-Precision Density Tester;
[0057] CFP-1200 Gas Permeation Pore Size Analyzer;
[0058] PMT-2 Liquid Particle Counter;
[0059] Electronic universal tensile testing machine (Model: D2-0200-1);
[0060] X-ray diffractometer (model: Bruker D2 PHASER Gen2);
[0061] Scanning electron microscope (model: VEGA3 XMU).
[0062] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0063] Example 1
[0064] This embodiment provides a method for preparing reinforced tungsten porous materials, including:
[0065] Tungsten powder with a spherical polyhedral particle size of 7 μm was weighed in a molar ratio of W:Cr = 9:1. 164.7 g of tungsten powder, 15.8 g of chromium chloride, and 500 mL of ultrapure water were weighed. The ultrapure water was placed in a round-bottom flask, and the tungsten powder was slowly poured into the ultrapure water while the magnetic stirrer was turned on to disperse it. After dispersing for 30 min, CrCl3 was slowly added and stirred for 60 min to completely dissolve it in the ultrapure water.
[0066] Prepare a 0.4 mol / L ammonia solution using a 250 mL volumetric flask and accurately dilute to volume. Slowly add the diluted ammonia solution dropwise into the round-bottom flask at a rate of 5 mL / min, stirring continuously with a magnetic stirrer for 180 min. During the addition of ammonia, observe that the reaction solution becomes cloudy. If the solution gradually becomes clear, stop adding ammonia immediately to prevent chromium hydroxide from redissolving in the ammonia and to control Cr content. 3+ The molar ratio with OH- should not exceed 1:3.
[0067] After the reaction is complete, the liquid is filtered using a vacuum filter. During filtration, it is washed with ultrapure water to remove any possible chromium chloride. The filtered liquid is then vacuum dried at 100°C for 120 minutes to remove any water molecules. After natural cooling, it is transferred to a ceramic crucible and subjected to a decomposition reaction in a tube furnace. The furnace temperature is set to 1200°C, and a reducing atmosphere of hydrogen is introduced for reduction to prevent oxidation of the tungsten powder during high-temperature processing. The hydrogen flow rate is 1 L / min, and the holding time is 180 minutes. The furnace is then cooled, and the hydrogen flow is turned off when the temperature drops to 40°C.
[0068] The hydrogen-reduced W-Cr alloy was ground using a planetary ball mill to break up any lumps. The resulting alloy powder was then loaded into a soft silicone mold and pressed using a cold isostatic press at a pressure of 200 MPa for 30 minutes and a holding time of 3 minutes. After molding, the powder was demolded and any loose powder on the surface was cleaned with a brush.
[0069] The sample was sintered in a medium-frequency induction furnace at a temperature of 1800℃ for 360 minutes with a hydrogen flow rate of 400 L / min. The sample was then cooled in the furnace until the temperature inside the furnace dropped to 40℃, at which point the hydrogen flow was turned off.
[0070] In this embodiment, the prepared tungsten porous material was ultrasonically cleaned with anhydrous ethanol for 60 minutes. After ultrasonication, a particle counter was used to detect the number of particles in the anhydrous ethanol. The number of particles larger than 0.5 μm was 0. The tungsten porous material was then subjected to a compressive strength test, and its compressive strength was 687 MPa. This indicates that the addition of chromium can effectively enhance the strength of the sintered neck. The average pore size of the tungsten porous material is 1.1 μm, and the porosity is 34%.
[0071] When Cr is added to W, it can react with oxygen atoms during use. The chromium element combines with impurity O to form a second-phase oxide, pinning grain boundaries and generating Cr2WO6 and CrWO4. This helps to improve the stability of the oxide layer of the sintered neck formed by W-Cr alloy, thereby enhancing the high-temperature oxidation resistance of the high alloy.
[0072] The microstructure of the sintered sample mainly consists of a W-rich phase (a solid solution of a small amount of Cr in W) and a Cr-rich phase (a solid solution of a small amount of W in Cr). Figure 2 It can be seen that, compared to the diffraction peaks of pure tungsten, the diffraction peaks of the W-rich phase shift to a higher 2θ angle. The Cr doping in the tungsten lattice is the cause of this shift. According to Bragg's equation, λ = 2dsinθ, the diffraction peaks shift to a higher 2θ angle. This is because the atomic radius of Cr is smaller than that of W (acr = 0.128 nm, aw = 0.139 nm), and Cr atoms replace W atoms in the W lattice, leading to a decrease in the tungsten lattice constant.
[0073] exist Figure 4a Elemental analysis was performed at the location marked by the blue line segment; the marked area is at the bond point of the sintered powder. From Figure 4a As shown in the curves for W and Cr elements in ~b, the content and distribution of elements undergo a dramatic change at the powder bonding point (i.e., where the sintering neck forms). This is mainly because the diffusion rate of Cr is greater than that of W during the solid solution formation process at the sintering neck. Furthermore, Cr elements can also be observed at other locations on the curves, indicating that the outer layer of the particles is composed of Cr, and the formed particles include a tungsten core layer, a chromium shell layer, and a tungsten-chromium solid solution sintering neck.
[0074] Example 2
[0075] This embodiment provides a method for preparing reinforced tungsten porous materials, including:
[0076] Tungsten powder with a spherical polyhedral particle size of 7 μm was weighed in a molar ratio of W:Cr = 8:2. 146.4 g of tungsten powder, 31.6 g of chromium chloride, and 500 mL of ultrapure water were weighed. The ultrapure water was placed in a round-bottom flask, and the tungsten powder was slowly poured into the ultrapure water. The magnetic stirrer was turned on to disperse the powder. After dispersing for 30 min, CrCl3 was slowly added and stirred for 60 min to dissolve the powder completely in the ultrapure water.
[0077] Prepare a 0.4 mol / L ammonia solution using a 500 mL volumetric flask and accurately dilute to volume. Slowly add the diluted ammonia solution dropwise into the round-bottom flask at a rate of 5 mL / min, stirring continuously with a magnetic stirrer for 180 min. During the addition of ammonia, observe that the reaction solution becomes cloudy. If the solution gradually becomes clear, stop adding ammonia immediately to prevent chromium hydroxide from redissolving in the ammonia and to control Cr content. 3+ The molar ratio with OH- should not exceed 1:3.
[0078] After the reaction is complete, the liquid is filtered using a vacuum filter. During filtration, it is washed with ultrapure water to remove any possible chromium chloride. The filtered liquid is then vacuum dried at 100°C for 120 minutes to remove any water molecules. After natural cooling, it is transferred to a ceramic crucible and subjected to a decomposition reaction in a tube furnace. The furnace temperature is set to 1100°C, and a reducing atmosphere of hydrogen is introduced for reduction to prevent oxidation of the tungsten powder during high-temperature processing. The hydrogen flow rate is 1 L / min, and the holding time is 180 minutes. The furnace is then cooled, and the hydrogen flow is turned off when the temperature drops to 40°C.
[0079] The hydrogen-reduced W-Cr alloy was ground using a planetary ball mill to break up any lumps. The resulting alloy powder was then loaded into a soft silicone mold and pressed using a cold isostatic press at a pressure of 200 MPa for 30 minutes and a holding time of 3 minutes. After molding, the powder was demolded and any loose powder on the surface was cleaned with a brush.
[0080] The sample was sintered in a medium-frequency induction furnace at a temperature of 1800℃ for 360 minutes with a hydrogen flow rate of 400 L / min. The sample was then cooled in the furnace until the temperature inside the furnace dropped to 40℃, at which point the hydrogen flow was turned off.
[0081] In this embodiment, the prepared tungsten porous material was ultrasonically cleaned with anhydrous ethanol for 60 minutes. After ultrasonication, a particle counter was used to detect the number of particles in the anhydrous ethanol. The number of particles larger than 0.5 μm was 0. The tungsten porous material was then subjected to a compressive strength test, and its compressive strength was 657 MPa. This indicates that the addition of chromium can effectively enhance the strength of the sintered neck. The average pore size of the tungsten porous material is 0.9 μm, and the porosity is 24%.
[0082] Example 3
[0083] This embodiment provides a method for preparing reinforced tungsten porous materials, including:
[0084] Tungsten powder with a spherical polyhedral particle size of 7 μm was weighed in a molar ratio of W:Cr = 8:2. 146.4 g of tungsten powder, 31.6 g of chromium chloride, and 500 mL of ultrapure water were weighed. The ultrapure water was placed in a round-bottom flask, and the tungsten powder was slowly poured into the ultrapure water. The magnetic stirrer was turned on to disperse the powder. After dispersing for 30 min, CrCl3 was slowly added and stirred for 60 min to dissolve the powder completely in the ultrapure water.
[0085] Prepare a 0.4 mol / L ammonia solution using a 500 mL volumetric flask and accurately dilute to volume. Slowly add the diluted ammonia solution dropwise into the round-bottom flask at a rate of 5 mL / min, stirring continuously with a magnetic stirrer for 180 min. During the addition of ammonia, observe that the reaction solution becomes cloudy. If the solution gradually becomes clear, stop adding ammonia immediately to prevent chromium hydroxide from redissolving in the ammonia and to control Cr content. 3+ With OH - The molar ratio should not exceed 1:3.
[0086] After the reaction is complete, the liquid is filtered using a vacuum filter. During filtration, it is washed with ultrapure water to remove any possible chromium chloride. The filtered liquid is then vacuum dried at 100°C for 120 minutes to remove any water molecules. After natural cooling, it is transferred to a ceramic crucible and subjected to a decomposition reaction in a tube furnace. The furnace temperature is set to 1100°C, and a reducing atmosphere of hydrogen is introduced for reduction to prevent oxidation of the tungsten powder during high-temperature processing. The hydrogen flow rate is 1 L / min, and the holding time is 180 minutes. The furnace is then cooled, and the hydrogen flow is turned off when the temperature drops to 40°C.
[0087] The hydrogen-reduced W-Cr alloy was ground using a planetary ball mill to break up any lumps. The resulting alloy powder was then loaded into a soft silicone mold and pressed using a cold isostatic press at a pressure of 200 MPa for 30 minutes and a holding time of 3 minutes. After molding, the powder was demolded and any loose powder on the surface was cleaned with a brush.
[0088] The sample was sintered in a medium-frequency induction furnace at a temperature of 1700℃ for 360 minutes with a hydrogen flow rate of 400 L / min. The sample was then cooled in the furnace until the temperature inside the furnace dropped to 40℃, at which point the hydrogen flow was turned off.
[0089] In this embodiment, the prepared tungsten porous material was ultrasonically cleaned with anhydrous ethanol for 60 minutes. After ultrasonication, a particle counter was used to detect the number of particles in the anhydrous ethanol. The number of particles larger than 0.5 μm was 0. The tungsten porous material was then subjected to a compressive strength test, and its compressive strength was 612 MPa. This indicates that the addition of chromium can effectively enhance the strength of the sintered neck. The average pore size of the tungsten porous material is 1.3 μm, and the porosity is 38%.
[0090] Example 4:
[0091] This embodiment provides a method for preparing reinforced tungsten porous materials. The preparation process is the same as in Embodiment 1, except that a different reduction temperature is used. Specifically, the furnace temperature is set to 1000℃, and hydrogen gas is introduced into a reducing atmosphere for reduction to avoid oxidation of tungsten powder during the high-temperature process. The hydrogen gas flow rate is 1L / min, the holding time is 180min, and the furnace is cooled. When the temperature drops to 40℃, the hydrogen gas is turned off.
[0092] In this embodiment, the prepared tungsten porous material was ultrasonically cleaned with anhydrous ethanol for 60 minutes. After ultrasonication, a particle counter was used to detect the number of particles in the anhydrous ethanol. The number of particles larger than 0.5 μm was 0. The tungsten porous material was then subjected to a compressive strength test, and its compressive strength was 603 MPa. This indicates that the addition of chromium can effectively enhance the strength of the sintered neck. The average pore size of the tungsten porous material is 1.0 μm, and the porosity is 36%.
[0093] By comparing the above embodiments, it can be seen that adding an appropriate amount of chromium salt can effectively promote the sintering of porous tungsten and improve the strength of the porous tungsten blank. Under suitable conditions, porous materials with good pore size and porosity can be obtained.
[0094] Comparative Example 1:
[0095] In the above examples, 7μm tungsten powder and 3μm chromium powder were weighed at a molar ratio of 9:1. 164.7g of tungsten powder and 15.8g of chromium powder were weighed and mechanically mixed using a planetary ball mill to obtain a tungsten-chromium mixed powder. During ball milling, chromium easily agglomerates, making it difficult to effectively disperse chromium within the tungsten powder. Using the molding process and sintering regime described in Example 1 to prepare porous tungsten materials, the agglomerated chromium melted easily when held at 1800℃ for 360 minutes. This caused chromium to block the pores of the porous tungsten. Furthermore, at 1800℃, tungsten could not effectively diffuse, failing to form a metallurgically bonded sintering neck, resulting in poor strength of the porous tungsten, with a compressive strength of 587MPa.
[0096] The technical solution in Comparative Example 1, which mechanically mixes chromium and tungsten powders, cannot effectively reduce the sintering temperature of tungsten porous materials, resulting in poor performance. However, the technical solution provided by this invention forms a chromium layer on the surface of the tungsten powder, which then forms a tungsten-chromium solid solution during the later sintering process. During high-temperature sintering, the active sites between the powders further diffuse and react, forming numerous network sintering necks, enhancing the metallurgical bonding strength between the tungsten powders and preventing powder detachment during use. Furthermore, the addition of Cr element makes the tungsten porous material perform even better, exhibiting higher strength.
[0097] The above description is merely the preferred embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions within the technical scope disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A method for preparing a tungsten porous material, comprising the following steps: (1) Disperse near-spherical tungsten powder in ultrapure water, add soluble chromium salt to dissolve it, then add ammonia solution dropwise and stir the reaction; the molar ratio of tungsten in the near-spherical tungsten powder to chromium in the soluble chromium salt is (2~10):1, and the chromium content is controlled by adding ammonia solution dropwise. 3+ With OH - The molar ratio is 1:(1~3), and the stirring time is 150~300 min; (2) After the reaction mixture is filtered, washed and dried, it is reduced in a reducing atmosphere to obtain tungsten-chromium core-shell pre-formed powder; (3) Grind the tungsten-chromium core-shell pre-made powder, and then use a mold to fill and press the ground and dried pre-made powder to obtain a tungsten porous material green body; (4) Clean the floating powder on the surface of the pressed green body and sinter it in a sintering furnace to obtain the tungsten porous material.
2. The preparation method according to claim 1, characterized in that, In step (1): The spherical tungsten powder has a Fisher particle size of 3~20µm; and / or, The mass ratio of the spherical tungsten powder to ultrapure water is 1:(1~10); and / or, The soluble chromium salt is selected from at least one of chromium chloride, chromium sulfate, and chromium nitrate; and / or, The molar ratio of tungsten in the spherical tungsten powder to chromium in the soluble chromium salt is (4~9):1; and / or, The concentration of the ammonia solution is 0.2~2.0 mol / L; and / or, The ammonia solution is added at a rate of 5-10 mL / min; and / or, Control of Cr by adding ammonia solution 3+ With OH - The molar ratio is 1:(2~3).
3. The preparation method according to claim 2, characterized in that, In step (1): The spherical tungsten powder has a Fisher particle size of 5~10µm; and / or, The mass ratio of the spherical tungsten powder to ultrapure water is 1:(1~5); and / or, The concentration of the ammonia solution is 0.2~1 mol / L.
4. The preparation method according to claim 1, characterized in that, In step (2): The drying conditions are: temperature 100~150℃, time 2~4h; and / or, The reducing atmosphere is a hydrogen atmosphere; and / or, The reduction treatment conditions are: hydrogen flow rate of 1~6 L / min, temperature of 900~1200℃, and time of 3~8 h.
5. The preparation method according to claim 1, characterized in that, In step (3): The grinding process is performed using ball milling; and / or, The mold is a silicone mold or a rubber mold; and / or, The pressing process is performed using a cold isostatic press.
6. The preparation method according to claim 1, characterized in that, In step (3): Wet ball milling is performed using a planetary ball mill; and / or, The pressing conditions are: pressure of 170~240MPa and holding time of 3~10min.
7. The preparation method according to claim 1, characterized in that, In step (4): The sintering atmosphere is hydrogen; and / or, The sintering conditions are: temperature of 1700~2100℃, time of 3~6h, and hydrogen flow rate of 300~600L / min.
8. The tungsten porous material obtained by the preparation method according to any one of claims 1 to 7, characterized in that, The tungsten porous material has an average pore size of 0.5~5µm and a porosity of 10~50%.
9. The tungsten porous material according to claim 8, characterized in that, The tungsten porous material has an average pore size of 0.5~3µm and a porosity of 10~40%.
Citation Information
Patent Citations
Method for preparing chromium-tungsten solid solution alloy material by powder pressure sintering
CN101126137A
Rhenium tungsten based cathode material and preparation method thereof
CN102628136A